1986
DOI: 10.1159/000199296
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranylacetone, a Novel Anti-Ulcer Drug, Stimulates Mucus Synthesis and Secretion in Rat Gastric Cultured Cells

Abstract: Aim of this study was to investigate the effect of geranylgeranylacetone (GGA) on mucus synthesis and secretion in rat gastric cultured cells, and their relationship to prostaglandin (PG) synthesis. Rate of mucus synthesis was estimated by incorporation of 3H-glucosamine into the cultured cells. Release of 3H-glucosamine from the cells, which were preincubated in the medium containing the radioactive isotope, into the culture media was measured for the evaluation of mucus secretion. PG pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 6 publications
(10 reference statements)
2
51
1
Order By: Relevance
“…TPA is one of the drugs that have cytoprotective action against gastric injury induced by necrotizing agents (1-3). We reported previously that pretreatment with TPA can prevent gastric damage induced by absolute ET, and this action of TPA may be due to the stimulation of gastric mucus production (7,8). Arakawa et al demonstrated the protective effect of TPA against gastric injury caused by ET in human subjects (9).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…TPA is one of the drugs that have cytoprotective action against gastric injury induced by necrotizing agents (1-3). We reported previously that pretreatment with TPA can prevent gastric damage induced by absolute ET, and this action of TPA may be due to the stimulation of gastric mucus production (7,8). Arakawa et al demonstrated the protective effect of TPA against gastric injury caused by ET in human subjects (9).…”
Section: Discussionmentioning
confidence: 95%
“…As we previously reported. TPA has the ability to stimulate gastric mucus in a cell culture system (8). In addition, TPA acts as a scavenging agent of free radicals like hydroxyl radicals in gastric cultured cells (15).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] we consider that the HSPs induced by GGA were responsible for its cytoprotective effect against the various gastric stressors (Fig. 3).…”
Section: Effect Of Gga and Low Concentrations Of Ethanol On Necrosis mentioning
confidence: 99%
“…Irsogladine is also reported to protect the gastric mucosa by enhancing the mucosal integrity of the stomach through the facilitation of gap junctional intracellular communication and increasing the intracellular levels of 3Ј,5Ј-cAMP (Ueda et al, 1995;Kyoi et al, 2004). On the other hand, teprenone exhibits a protective effect in various models by stimulating the secretion of mucus and the expression of heat shock proteins (Terano et al, 1986;Suemasu et al, 2009). Although the precise mechanisms by which these drugs reduced the severity of the antral lesions in response to indomethacin plus paroxetine remain unknown, it is assumed that these mucosal protective drugs can be used as a prophylactic against gastric bleeding associated with SSRIs.…”
Section: Discussionmentioning
confidence: 99%